Analisis Aspek Molekuler Biomarka Alkana Bercabang Core Badak 1/208 Muara Badak, Kutai Kartanegara, Kalimantan Timur - R. Arizal Firmansyah; R. Y. Perry Burhan (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2015)
Study compound biomarka branched alkanes on core 1/208 Rhinos have done to contribute to the activities of oil exploration wells 1/208 Muara Badak Badak, East Kalimantan's Kutai Kartanegara-through core biomarka profile branched alkanes. Core samples extracted by alternately with solvent mixture of toluene-methanol (3: 1) and chloroform-methanol (3: 1). Then fractionated by Column Chromatography and Thin Layer Chromatography to obtain aliphatic hydrocarbon fraction. Fractions obtained were identified using Gas Chromatography-Mass Spectrometry.The content biomarka aliphatichydrocarbon fraction were identified, among others, iso and anteiso alkanes, mono and trimethyl alkanes. Compounds iso and anteiso alkanes, and alkyl alkane other, providing information that the source of organic material core samples I and II is derived from microorganisms prokaryotic or biogenic precursor derived from cyanobacteria (marine microorganisms) and homologous monomethyl alkanes found in core samples II closer homologous series monomethyl alkanes found in sediments and oil and Precambrian Proterozoic era, so it can be said that the core sample II core samples older than I.